2018
DOI: 10.1111/manc.12258
|View full text |Cite
|
Sign up to set email alerts
|

Money Growth and Inflation: New Evidence from a Nonlinear and Asymmetric Analysis

Abstract: The relationship between money growth and inflation is a topic of debate among macroeconomists. This paper contributes to the empirical literature on the money‐inflation pass‐through using a Nonlinear Auto‐Regressive Distributed Lag model (NARDL) for three countries (the U.S., U.K. and Japan) over an estimation period spanning 1950Q1 to 2014Q4. This methodology allows for empirical tests of short‐ and long‐run asymmetric responses of inflation to both positive and negative shocks affecting money growth of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
(127 reference statements)
1
6
0
Order By: Relevance
“…Although there has been no similar study for the Turkish economy, findings of this study confirm Hamilton (1994) viewpoint, and like Amisano and Colavecchio (2013), Amisano and Fagan (2013), Cooray andKhraief (2019), andEltejaei (2020) showed that the causal relationship between money growth and inflation despite theoretical literature is not linear necessarily.…”
Section: Stationarysupporting
confidence: 82%
See 2 more Smart Citations
“…Although there has been no similar study for the Turkish economy, findings of this study confirm Hamilton (1994) viewpoint, and like Amisano and Colavecchio (2013), Amisano and Fagan (2013), Cooray andKhraief (2019), andEltejaei (2020) showed that the causal relationship between money growth and inflation despite theoretical literature is not linear necessarily.…”
Section: Stationarysupporting
confidence: 82%
“…Thus, money growth is an important early warning indicator of risks to price stability. For the U.S., the U.K., and Japan, Cooray, and Khraief (2019) applied Nonlinear Auto-Regressive Distributed Lag (NARDL) model and found that inflation responded asymmetrically to monetary shocks in the long-run for the period 1950:1-2014:4. Eltejaei (2020), using an MS-VAR model, showed that three different regimes could be identified for money growth and inflation in Iran during the 1961-2017 period.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For Bulgaria and the Czech Republic, the effect of fiscal policy on inflation does not stabilise in the long run, and has a mixture of short-run effects, which are both positive and negative. This shows that for the two economies, the possible inflationary effects are counterbalanced by efficient monetary policies (Cooray & Khraief, 2019;Sriyana, 2019).…”
Section: Empirical Findingsmentioning
confidence: 90%
“…In the literature, the confusion over the significance of the relationship between money growth and inflation stems from the deterioration of the relationship in lowinflation environments, on the one hand (Sargent & Surico, 2011), and the evidence that has presented a strong link between money and inflation, on the other hand (Cooray & Khraief, 2019;Fedotenkov, 2018).…”
Section: Introductionmentioning
confidence: 99%